Effect of bioethanol–diesel blends, exhaust gas recirculation rate and injection timing on performance, emission and combustion characteristics of a common rail diesel engine. Issue 4 (4th July 2019) - Lamani, Venkatesh T.; Baliga M, Aditya U.; Yadav, Ajay Kumar; Kumar, G. N.
ABSTRACT: This investigation is focused on the effect of exhaust gas recirculation (EGR) and injection timing on the performance, combustion and exhaust emission characteristics of common rail direct injection (CRDI) engine fueled with bioethanol-blended diesel using computational fluid dynamics (CFD) simulation. Simulation is carried out for various EGR rates (0, 10, 20 and 30%), two different injection timings, and two different bioethanol–diesel blends (10 and 20%) at injection pressure. The equivalence ratio is kept constant in all the cases of bioethanol–diesel blends. The results indicate that the mean CO formation and ignition delay increase, whereas mean NO formation and in-cylinder temperature decrease, with increase in the EGR rate. Further, with an increase in percentage of the bioethanol blends, CO and soot formation decrease as compared to neat diesel. A significant increase in in-cylinder pressure (15%) is found at 14° before top dead centre (BTDC) compared to 9° BTDC, which leads to an increase in indicated thermal efficiency of 4% for neat diesel at 30% EGR. In the present study, maximum indicated thermal efficiency is obtained in the case of 10 and 20% bioethanol–diesel blend, and remains constant for all EGR rates considered in the study. Obtained results are validated with the available literature data and indicate good agreement.